ACTS OF TERRORISM AS A TACTIC OF THE ISLAMIC STATE AND IMPLICATIONS FOR RUSSIAN FOREIGN POLICY - Xaribin, Aleksandr Nikolaevich (Nauka Krasnoi͡a︡rʹi͡a, 2016)
In the article the analysis of the Islamic state: emergence, current status, reasons for success, control methods and prospects. The last terrorist attacks: Russian aircraft over the Sinai and the terrorist attack in Paris. A comparative analysis and reasons for election purposes by terrorists to attack, the consequences for Egypt, Europe, the middle East and Russia. At the end of the article gives practical recommendations for Russian foreign policy and the forecast of development of events in this region, it is hypothesized that the further growth of the Islamic state and the inability to move it to the borders of Russia